"Gone are the days of mass-media marketing plans and short term customer relationships": tobacco industry direct mail and database marketing strategies. Issue 4 (4th August 2015) - Lewis, M Jane; Ling, Pamela M
Abstract : Background: As limitations on traditional marketing tactics and scrutiny by tobacco control have increased, the tobacco industry has benefited from direct mail marketing which transmits marketing messages directly to carefully targeted consumers utilising extensive custom consumer databases. However, research in these areas has been limited. This is the first study to examine the development, purposes and extent of direct mail and customer databases. Methods: We examined direct mail and database marketing by RJ Reynolds and Philip Morris utilising internal tobacco industry documents from the Legacy Tobacco Document Library employing standard document research techniques. Results: Direct mail marketing utilising industry databases began in the 1970s and grew from the need for a promotional strategy to deal with declining smoking rates, growing numbers of products and a cluttered media landscape. Both RJ Reynolds and Philip Morris started with existing commercial consumer mailing lists, but subsequently decided to build their own databases of smokers' names, addresses, brand preferences, purchase patterns, interests and activities. By the mid-1990s both RJ Reynolds and Philip Morris databases contained at least 30 million smokers' names each. These companies valued direct mail/database marketing's flexibility, efficiency and unique ability to deliver specific messages to particular groups as well as direct mail's limited visibility to tobacco control, public health and regulators. Conclusions: Database marketing is an important and increasingly sophisticated tobacco marketing strategy. Additional research is needed on the prevalence of receipt and exposure to direct mail items and their influence on receivers' perceptions and smoking behaviours.